Maternal overnutrition programs central inflammation and addiction-like behavior in Offspring - Montalvo Martínez, Larisa Jajaira; Maldonado Ruiz, Roger Alexis; Cárdenas Tueme, Marcela; Reséndez Pérez, Diana; Camacho Morales, Alberto (2018)
Obesity or maternal overnutrition during pregnancy and lactation might have long-term consequences in offspring health. Fetal programming is characterized by adaptive responses to specific environmental conditions during early life stages. Programming alters gene expression through epigenetic modifications leading to a transgenerational effect of behavioral phenotypes in the offspring. Maternal intake of hypercaloric diets during fetal development programs aberrant behaviors resembling addiction in offspring. Programming by hypercaloric surplus sets a gene expression pattern modulating axonal pruning, synaptic signaling, and synaptic plasticity in selective regions of the reward system. Likewise, fetal programming can promote an inflammatory phenotype in peripheral and central sites through different cell types such as microglia and T and B cells, which contribute to disrupted energy sensing and behavioral pathways. Te molecular mechanism that regulates the central and peripheral immune cross-talk during fetal programming and its relevance on offspring’s addictive behavior susceptibility is still unclear. Here, we review the most relevant scientific reports about the impact of hypercaloric nutritional fetal programming on central and peripheral inflammation and its effects on addictive behavior of the offspring.